Students’ Perceptions In English Teaching And Learning By Using Internet-Assisted - Anggun Wulandari1; Husnani Aliah; Nasriandi (Jurnal Serambi Ilmu, 2024)
This research was conducted with the aim of knowing the description of student perceptions in learning and teaching English using the help of the internet,The population or subject of this study were all students of the English language education study program, the Teaching and Education Faculty of the University of Muhammadiyah Palopo. Samples are taken at random, unrestricted or unspecifiedthe number of respondents entered was only 35 students, the research questionnaire totaled 20 statements made in the form of a link and then sent to the whatsapp group chat, sample data collection for this study was by survey technique using Google form media, this study used quantitative descriptive, the instrument used was the Likert model scale and data analysis assisted by using the SPSS version 22 computer, the data results showed an average score for each questionnaire from 3,97 to 4,26 while the average score for the total parts of the questionnaires X1, X2 and Y that is equal to (31,91) , ( 28,40) and (20,03) And it is known that the results of the valid percentage data and the cumulative percentage of 35 respondents according to their perception are 100% strongly agree with the research questionnaire on "Students’ perceptions in English teaching and learning by using internet-assisted", then it can be concluded that students have positive perceptions of the research questionnaire.